The Cross and the Rising Sun, Volume 2 : the British Protestant Missionary Movement in Japan, Korea and Taiwan, 1865-1945. - Ion, A. Hamish (Wilfrid Laurier University Press, 2009)
The influx of Protestant missionaries from Britain to Japan, Korea and Taiwan was an integral part of the British presence in East Asia from 1865 to 1945. Ion draws on both British and Japanese sources to examine the life, work and attitudes of the British missionaries, women and men, who ventured far from their homeland to preach the gospel. He explores the role played by British Protestants as both Christian missionaries and informal ambassadors of their own country and civilization. Through their educational, social and medical work the missionaries helped introduce Western ideas and socia.